The Role of Government Policy in Responding to Climate Change: A Literature Review - Wulandari, Rina; Mia Karlina, Neng (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Climate change generates increasingly complex governance challenges, requiring a comprehensive understanding of the effectiveness of policies, instruments, and institutional dynamics that shape countries’ adaptive capacities. This study conducts a systematic review of research published between 2021 and 2025 to identify cross-contextual patterns regarding barriers and enablers of adaptation, policy approaches and instruments, policy effectiveness, and the political–institutional factors influencing climate policy outcomes. The search and selection process followed a rigorous SLR protocol, accompanied by thematic coding to map four major themes emerging from the reviewed articles. The synthesis indicates that adaptation barriers most frequently stem from governance fragmentation, regulatory ambiguity, limited institutional capacity, and the dominance of top-down approaches that overlook social vulnerability. Regarding policy instruments, Climate Action Plans, policy mixes, carbon taxes, Nature-Based Solutions, and adaptation finance mechanisms prove effective only when supported by robust institutional frameworks and cross-sectoral coordination. In many countries, integration between mitigation and adaptation within development policies remains weak, while technocratic approaches that prioritize infrastructure often create risks of the safe-development paradox and increase long-term exposure to climate hazards. Policy effectiveness is significantly shaped by socio-political dynamics such as partisanship, geopolitical interests, and the quality of public participation, which can either strengthen or weaken the legitimacy of climate policies. The synthesis underscores that successful climate governance requires stable legal and institutional frameworks, the integration of adaptation and mitigation, participatory and equity-oriented approaches, reliable technical instruments and data, as well as coordinated and sustained implementation. This study advances the understanding of how structural, social, and political factors shape climate adaptation effectiveness and provides a conceptual foundation for developing more inclusive, integrated, and responsive climate policies in the face of escalating climate risks.